The Influence of Principal’s Leadership and Certification on Teachers’ Work Motivation - Deasy Aryanti; Tri Widayatsih; Suherman Suherman (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to analyze the influence of principal’s leadership and teachers’ certification on the work motivation of public elementary school teachers in Kedondong Raye Village, both partially and simultaneously. Using a quantitative ex post facto method, data were collected via questionnaires and documentation from 71 certified teachers and analyzed with SPSS. The results confirm that both principal’s leadership and certification individually have a significant positive effect on teacher motivation. Furthermore, their combined influence is also significant, indicating they function as complementary drivers. The novelty of this research lies in its specific examination of these two factors within the unique context of a rural village setting, providing localized insights into the drivers of teacher motivation. A key practical implication is that to enhance teacher motivation, educational stakeholders must adopt an integrated approach: school principals should strengthen supportive and transformative leadership practices, while systemic certification policies should be maintained and their professional benefits reinforced. This study contributes by offering empirical evidence on the synergistic relationship between leadership and certification, presenting a practical model for improving teacher motivation and, consequently, educational outcomes in similar rural or village-based school environments.